New forms of employment and the risk of labor exploitation – legal aspects - Ristić, Andrijana (Glasnik Advokatske komore Vojvodine, 2026)
The development of technology and accelerated changes in the world of work have led to the emergence of new, specific forms of work, which have arisen as a response to the altered needs of employers and workers shaped by contemporary circumstances. However, the particular characteristics and legal underregulation of these forms of work in most countries around the world, have resulted in workers engaged in them remaining largely “invisible” to legal systems, whereby they are not guaranteed even a minimum level of labour and social rights that should be available to all individuals engaged in work. Such a situation poses a serious risk to the enjoyment of the right to decent work and creates a favorable environment for the emergence of labor exploitation. These circumstances, in light of the growing significance of new forms of work, represent the key reasons that motivated the author to choose this topic. Accordingly, the paper analyses the interconnection between new forms of work, the unfavourable labour-law status of workers engaged in them, and the risk of labour exploitation. Finally, the author seeks to highlight, in a concise manner, the need to reassess the existing boundaries of labour-law protection in light of new forms of work, as well as to propose legal solutions that may contribute to overcoming the identified problems in this regard.